Genetic association between temperament and sexual precocity indicator traits in Nellore cattle - Valente, T. S. [UNESP]; Sant'Anna, A. C. [UNESP]; Baldi, F.; Albuquerque, L. G. [UNESP]; Paranhos da Costa, Mateus J. R. [UNESP] (Springer, 2015)
The aim of this study was to estimate the genetic associations between temperament and sexual precocity indicators in Nellore cattle. Temperament was evaluated at approximately 550 days of age, using three traits: i) movement score (MOV), recording the animals' movement inside the crush; ii) temperament score (TS) for assessing the reactions of animals in a corral pen; and iii) flight speed test (FS), recording the speed (in m/s) at which the animals exit the crush after being weighed. Three sexual precocity indicators were used: i) age at first calving (AFC, in days); ii) occurrence of precocious pregnancy (OPP, as a binary trait); and iii) yearling scrotal circumference (SC, in cm). The (co)variance and genetic parameters were estimated by Bayesian Inference via Gibbs sampling, assuming a linear animal model for FS, AFC and SC and a threshold animal model for MOV, TS and OPP in multitrait analyses. The mean posterior heritability estimates for MOV, FS, TS, AFC, OPP and SC were 0.11 +/- 0.03, 0.27 +/- 0.07, 0.16 +/- 0.09, 0.09 +/- 0.01, 0.44 +/- 0.06 and 0.43 +/- 0.02, respectively. The mean posterior correlation estimates were: 0.13 +/- 0.14 (MOV-AFC), -0.03 +/- 0.16 (MOV-OPP), 0.08 +/- 0.10 (MOV-SC), 0.14 +/- 0.11 (FS-AFC), -0.19 +/- 0.15 (FS-OPP), -0.07 +/- 0.08 (FS-SC), 0.09 +/- 0.09 (TS-AFC), -0.03 +/- 0.09 (TS-OPP) and -0.28 +/- 0.08 (TS-SC). These results indicate that all the traits had sufficient genetic variability to respond to selection. The low magnitude of the genetic correlations indicated that selection for improvements in sexual precocity would not change the temperament of Nellore cattle. In order to obtain genetic progress in cattle temperament, direct selection for these traits is recommended.
Keywords: Beef cattle; Flight speed; Genetic correlation; Heritability; Reactivity